2010
DOI: 10.1177/0266242609356031
|View full text |Cite
|
Sign up to set email alerts
|

Introduction from Special Editors

Abstract: special issues of more general journals. Literature reviews have appeared in journals, as chapters, and as separate volumes (Ram and Jones, 2008).Early in the British discourse a contrast developed between studies emphasizing the cultural background of migrant groups as an explanation of minority business development (Srinivasan, 1995;Werbner, 1984Werbner, , 1990, and those that emphasized constraining social and economic factors (Aldrich et al., 1981(Aldrich et al., , 1984. In the first instance the empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The study aimed to ensure agility in accessing and processing information, support the decision-making of managers, allow efficiency and public transparency, and minimize the difficulties in access, in the management of various BI systems and the informational asymmetries existing in the Public Administration. Another study conducted in Egypt found that higher education institutions in developing countries are challenged with the high enrolment student rates, crowded classes, and inability to track the progress of each student individually, which increased the demand to find a solution that can redeem those problems (McEvoy et al, 2010;Sharma & Joshi, 2022).…”
Section: Popularity Of Dashboard Among Higher Education Institutionsmentioning
confidence: 99%
“…The study aimed to ensure agility in accessing and processing information, support the decision-making of managers, allow efficiency and public transparency, and minimize the difficulties in access, in the management of various BI systems and the informational asymmetries existing in the Public Administration. Another study conducted in Egypt found that higher education institutions in developing countries are challenged with the high enrolment student rates, crowded classes, and inability to track the progress of each student individually, which increased the demand to find a solution that can redeem those problems (McEvoy et al, 2010;Sharma & Joshi, 2022).…”
Section: Popularity Of Dashboard Among Higher Education Institutionsmentioning
confidence: 99%